Peran Instagram Sebagai Pemasaran Media Sosial Dalam Membangun Kesadaran Merek dan Dampaknya terhadap Keputusan Pembelian pada Salah Satu Kedai Kopi Lokal Top Brand Indonesia - Marie, Andhalia Liza; Widodo, Rintis Eko; Prasetio, Arton Briyan (Jurnal Ilmiah Pariwisata, 2023)
The purpose of this research is to determine how brand awareness mediates the influence of social media marketing on purchasing decisions. The sampling technique in this research is non-probability sampling with a purposive sampling method. Data was taken using Google Form with a total of 138 respondents. The data analysis technique used is PLS-SEM. The results of this research state that: (1) Social media marketing has a positive effect on brand awareness; (2) Brand awareness has a positive effect on purchasing decisions; (3) Social media marketing has a positive effect on purchasing decisions; (4) Brand awareness mediates the influence of social media marketing on purchasing decisions. Social media marketing positively influences brand awareness through reaching a wide audience, and visual content. High brand awareness positively influences purchasing decisions by increasing consumer familiarity, trust and preference. Brand awareness also acts as a link between social media marketing and purchasing decisions through creating positive perceptions and better knowledge about the brand, playing a key role in influencing consumer purchasing actions. Keywords: Social Media Marketing, Brand Awareness, Purchase Decisions